2019
DOI: 10.1111/bju.14775
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term oncological outcomes of patients with paratesticular sarcoma

Abstract: Objectives To present long‐term oncological outcomes of patients with paratesticular sarcoma treated by a multidisciplinary team. Patients and methods Patients managed at the Princess Margaret Cancer Centre, between 1990 and 2012, were analysed. A sarcoma expert performed central pathology review. Kaplan–Meier graphs compared local recurrence (LR), metastasis, and overall survival (OS) of patients treated with hemiscrotectomy vs those who did not. Univariable Cox proportional hazards analysis was performed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 23 publications
(44 reference statements)
1
11
0
Order By: Relevance
“…Urological sarcomas are rare tumors accounting for 2.7% of all soft tissue sarcomas across organs in adult patients [1]. Paratesticular liposarcoma (PTL) is relatively common among the urological sarcomas in the literature [1][2][3][4][5], however, PTL is an extremely rare clinical entity. Based on previous case studies and recent reviews [3][4][5][6][7][8][9], approximately more than 200 cases of PTL have been reported to date.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Urological sarcomas are rare tumors accounting for 2.7% of all soft tissue sarcomas across organs in adult patients [1]. Paratesticular liposarcoma (PTL) is relatively common among the urological sarcomas in the literature [1][2][3][4][5], however, PTL is an extremely rare clinical entity. Based on previous case studies and recent reviews [3][4][5][6][7][8][9], approximately more than 200 cases of PTL have been reported to date.…”
Section: Introductionmentioning
confidence: 99%
“…Paratesticular liposarcoma (PTL) is relatively common among the urological sarcomas in the literature [1][2][3][4][5], however, PTL is an extremely rare clinical entity. Based on previous case studies and recent reviews [3][4][5][6][7][8][9], approximately more than 200 cases of PTL have been reported to date. PTLs mostly present as a painless, slow-growing inguinal or inguinoscrotal mass [2,3,8,9].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations